Resurrection of Perilimnastes (Sonerileae, Melastomataceae) with description of a new species P. nana - Ying Liu; Jin-Hong Dai; Qi-Yuan Zhuang; Chun-Yu Zou; Kai-Nan Ma (PhytoKeys, 2024)
Recent research has indicated that the Phyllagathis (raphides) clade (Sonerileae, Melastomataceae) is only distantly related to the type of Phyllagathis and should be separated as a distinct genus. Phylogeny of this clade is here reconstructed with expanded taxon sampling. Four strongly supported subclades have been identified. The possible affinities of taxa that were not sampled in the analysis are discussed, based on morphological data. Perilimnastes is resurrected as the generic name of the Phyllagathis (raphides) clade. A generic description, colour figures, map of distribution, a list of included species and a key are provided for Perilimnastes. Fifteen new combinations are made plus the description of a new species. As interpreted here, Perilimnastes consists of twenty species and two varieties.